THE PROJECTILE CALIBER AND TYPE DETERMINATION BY SUPERIMPOSITION ON THE EXIT CRANIAL VAULT DEFECT - Al-Turki, Ali Ali; Siamionau, Viachaslau V.; Tsiatsiuyeu, Andrei M. (Universal Journal of Pharmaceutical Research, 2024)
A case of group identification of a firearm projectile using a comparative study by the overlay method is presented. Morphological characteristics of the exit gunshot bullet fractures are generally used to establish the direction and number of shots. Identification was carried out by exit gunshot injury to the bones of the skull vault of the skeletonized corpse. The shape and size of the gunshot perforated fracture displayed the caliber of the bullet and its lateral profile. Examination of the bone remains established a single penetrating gunshot bullet wound of the 1st cervical vertebra (atlas) and the skull. In this case the entry injury, located on the anterior arch of the atlas and the basilar part of the occipital bone, did not have identification significance. Peer Review History: Received: 2 October 2023; Revised: 6 November; Accepted: 27 December; Available online: 15 January 2024 Academic Editor: Dr. Jennifer Audu-Peter , University of Jos, Nigeria, drambia44@gmail.com Reviewers: Prof. Hassan A.H. Al-Shamahy, Sana'a University, Yemen, shmahe@yemen.net.ye Dr. Rima Benatoui, Applied Neuroendocrinology Laboratory, Faculty of Sciences, University of Annaba, Algeria. benattouiryma@gmail.com Dr. Asia Selman Abdullah, University of Basrah, Iraq, asia_abdullah65@yahoo.com